Field boundary delineation and cropped area measurement - Matheswaran, Karthikeyan; Ibrahim, Ali (2023)
Accurate measurement of crop cultivated area and corresponding field boundary is essential for assessing various agronomic key performance indicators (KPIs), including yield, profitability and resource use efficiency. In the past, household surveys have relied heavily on farmer-reported plot areas. However, it has been frequently noted that farmer-reported plot area is often inaccurate for various reasons. In addition, field boundary information — which is crucial for various agronomic analytics purposes — is rarely available. Here, we describe the procedure for a global positioning system (GPS)–based field area measurement using a smartphone/tablet application. We describe GPS Fields Area Measure,1 an Android application freely downloadable from Google Play Store, as an example. The module describes the procedures for downloading and performing the measurements using this app. Many other apps with similar functions can also be used to measure field/plot area. Users need to refer to the corresponding user guides when using other Android applications. GPS Fields Area Measure is also available on the Apple App Store,2 but the description below is only for the Android system.